2015
DOI: 10.3390/rs71013782
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Prediction of Coastal Bathymetry Based on Multispectral Satellite Imagery and Multibeam Data

Abstract: Abstract:The coastal shallow water zone can be a challenging and costly environment in which to acquire bathymetry and other oceanographic data using traditional survey methods. Much of the coastal shallow water zone worldwide remains unmapped using recent techniques and is, therefore, poorly understood. Optical satellite imagery is proving to be a useful tool in predicting water depth in coastal zones, particularly in conjunction with other standard datasets, though its quality and accuracy remains largely un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 57 publications
3
58
0
1
Order By: Relevance
“…Sementara itu, penelitian lain dengan mengintegrasikan resolusi tinggi citra WorldView-2 dengan kedalaman yang didasarkan pada algoritma multi channel baru telah dikembangkan (Eugenio et al, 2015). Penelitian dengan menerapkan rasio kanal biru/hijau dan model statistik ground calibration points dengan menggunakan citra satelit RapidEye (Monteys et al, 2015). Penelitian kedalaman menggunakan linear radiative transfer Bathymetry models atau model perpindahan radiasi kedalaman linear menggunakan citra IRS-1C, yang hasil informasinya dapat diintegrasi echo sounding dan Data GPS (Pattanaik et al, 2015), menghitung kedalaman dengan menggunakan Ensemble Learning (EL) dari algoritma Least Squares Boosting (LSB) dengan menggunakan citra SPOT-4 (Mohamed et al, 2016).…”
Section: Abstrakunclassified
“…Sementara itu, penelitian lain dengan mengintegrasikan resolusi tinggi citra WorldView-2 dengan kedalaman yang didasarkan pada algoritma multi channel baru telah dikembangkan (Eugenio et al, 2015). Penelitian dengan menerapkan rasio kanal biru/hijau dan model statistik ground calibration points dengan menggunakan citra satelit RapidEye (Monteys et al, 2015). Penelitian kedalaman menggunakan linear radiative transfer Bathymetry models atau model perpindahan radiasi kedalaman linear menggunakan citra IRS-1C, yang hasil informasinya dapat diintegrasi echo sounding dan Data GPS (Pattanaik et al, 2015), menghitung kedalaman dengan menggunakan Ensemble Learning (EL) dari algoritma Least Squares Boosting (LSB) dengan menggunakan citra SPOT-4 (Mohamed et al, 2016).…”
Section: Abstrakunclassified
“…Harris et al (2013) demonstrated GW mae for UK freshwater acidification and London house price prediction accuracy, as separate case studies. Monteys et al (2015) demonstrated GW r for assessing water depth prediction accuracy in Irish coastal waters. These studies either directly extend GW summary statistics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These multispectral sensors produce imagery with a spatial resolution of nearly 4 m, which is far superior to that of medium resolution sensors (i.e., 20 -250 m). Data produced by these high-resolution satellites are not only useful for accurately assessing coastal wetlands (Yagoub and Kolan 2006;Adam et al 2014;Monteys et al 2015), but also assist in gaining an understanding of the impacts of interactions between natural and anthropogenic processes (Lee and Shan 2003). Korea Multi-Purpose Satellite-2 (KOMPSAT-2), launched in 2006, is also a high spatial resolution satellite with 4-m resolution multispectral bands.…”
Section: Introductionmentioning
confidence: 99%